Short-Term Effect Of Conservation Agriculture Practices On Soil Quality Of A Vertisol In Central India (Applied Biological Research, 2017)
A field experiment was conducted to assess the effect of contrasting tillage  systems viz., no- tillage, reduced tillage and conventional tillage with four  cropping systems viz., soybean + pigeon pea (2:1), soybean - wheat, maize  + pigeon pea (1:1) and maize - chickpea on yields and soil quality in a Vertisols of Central India. Surface soil samples were collected and analyzed for physicochemical properties. Correlation analysis of seven soil physicochemical attributes showed a significant correlation in eight (P < 0.01) and four (P < 0.05) attribute pairs out of the 49 soil attribute pairs. The results revealed that the soil properties such as soil reaction (pH), electrical conductivity, organic carbon, mean weight diameter, available nitrogen, available phosphorus and available potassium were influenced by tillage and cropping systems. Evaluation of soil quality using soil quality index (SQI) under different tillage and cropping system  showed that soil quality was better in maize + pigeon pea (1:1) and soybean + pigeon pea (2:1) under reduced tillage and no tillage ascompared to the other systems. The tillage that caused destructive effects on soil quality should be discouraged for long-term cultivation to maintain good soil health for sustainable agricultural production. The value of SQI was positively and significantly correlated with soybean grain equivalent yield for all the tillage and cropping system. This indicates that the index parameters may be used for
Keywords: Contrasting tillage; cropping system; soil quality; soil quality index; soil physic-chemical properties